General Control Non-derepressible 1 (AtGCN1) Is Important for Flowering Time, Plant Growth, Seed Development, and the Transcription/Translation of Specific Genes in Arabidopsis - Cui, Xiaona; Gao, Kaili; Wang, Linjuan; Lv, Mengyang; Li, Ziwen; Zheng, Donghua; Wu, Wenwu; Yao, Wen; Ding, Liying; Li, Xiao; Zhu, Jian-Kang; Zhang, Hairong (Frontiers in Plant Science, 2021)
We have previously demonstrated that General Control Non-derepressible 1 (AtGCN1) is essential for translation inhibition under cold stress through interacting with GCN2 to phosphorylate eukaryotic translation initiation factor 2 (eIF2). Here, we report that the flower time of the atgcn1 mutant is later than that of the wild type (WT), and some siliques of atgcn1 cannot develop and produce seeds. Total and polysomal RNA of atgcn1-1 and wild type (WT) after cold treatments were sequenced. The sequencing results show that the mutation of atgcn1 selectively alters the expression of genes at both transcriptional and translational levels. The classification of AtGCN1 target genes reveals that AtGCN1 regulated gens are involved in flower development, seed dormancy and seed development, response to osmotic stress, amino acid biosynthesis, photosynthesis, cell wall organization, protein transport and localization, lipid biosynthesis, transcription, macroautophagy, proteolysis and cell death. Further analysis of AtGCN1 regulated genes at translational levels shows that the Kozak sequence and uORFs (upstream open reading frame) of transcripts affect translation selection. These results show that AtGCN1 is required for the expression of selective genes in Arabidopsis.